EMI Reduction Techniques in Digitally Controllable Power Supplies. (2015) - Turos, Laszlo; Csernáth, Géza; Szekely, Iuliu
Abstract: The paper presents EMI reduction techniques in analog and digital power supplies, highlighting the role of each technique apart. There are also detailed some useful hardware and software design techniques in order to reduce or attenuate the EMI. Passive techniques focus on reducing the EMI level by filtering, shielding and proper PCB layout of the power components. Active techniques focus on modifying the PWM control signal shape in order to reduce EMI or spread the energy of the signal on wide frequency range. The paper also presents an implementation method of the spread frequency modulation on a low cost RISC MCU unit. The paper describes the mathematical and simulated relationship between a non-ideal PWM signal's main parameters and the spectral content of the signal. The experimental results are obtained by measurements performed on a multistage buck-boost converter, which uses two converters working in parallel and in phase-shift of 180° developed by the authors.